2020
DOI: 10.18203/2349-3291.ijcp20200043
|View full text |Cite
|
Sign up to set email alerts
|

Study to correlate sepsis markers and blood culture in neonatal sepsis

Abstract: Background: Neonatal sepsis forms the second most common cause of neonatal mortality resulting in more than one million neonatal deaths per year. Neonatal sepsis, pneumonia and meningitis together result in one- fourth of all newborn deaths. Objectives of the study was to correlate sepsis markers with blood culture in neonatal sepsis.Methods: A cross sectional study was carried out in the NICU unit under department of Pediatrics, between November 2017 and May 2019. Sample size was 50. Babies admitted to NICU w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Swamy et al conducted a study to correlate sepsis markers and blood culture in neonatal sepsis. They concluded that blood culture was positive in 20.0% of the patients (E. coli being the most commonly isolated organism) [ 25 ]. CRP had a high sensitivity of 90.0% and low specificity of 47.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Swamy et al conducted a study to correlate sepsis markers and blood culture in neonatal sepsis. They concluded that blood culture was positive in 20.0% of the patients (E. coli being the most commonly isolated organism) [ 25 ]. CRP had a high sensitivity of 90.0% and low specificity of 47.0%.…”
Section: Discussionmentioning
confidence: 99%